2010
DOI: 10.2146/ajhp090325
|View full text |Cite
|
Sign up to set email alerts
|

Use of granulocyte colony-stimulating factor in patients with severe sepsis or septic shock

Abstract: The available data, especially those from large, prospective, randomized, double-blind studies, do not support the use of G-CSF as an adjunct therapy to standard care for critically ill patients with severe sepsis or septic shock. Data from prospective, large, randomized, controlled, well-designed studies are needed to define the optimal G-CSF dosing regimen, the safety of this therapy, and the effects of G-CSF on patient morbidity and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 50 publications
0
8
1
Order By: Relevance
“…Additionally, our findings differed from several trials in which G-CSF administered to patients with severe sepsis showed no clear survival benefit (1417). A meta-analysis of these trials was recently published verifying a lack of a survival benefit for individuals receiving G-CSF (15).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Additionally, our findings differed from several trials in which G-CSF administered to patients with severe sepsis showed no clear survival benefit (1417). A meta-analysis of these trials was recently published verifying a lack of a survival benefit for individuals receiving G-CSF (15).…”
Section: Discussioncontrasting
confidence: 99%
“…Though in prior mouse models of sepsis, treatment with antibiotic with G-CSF and novel antimicrobial peptide LL-37 did increase survival (13). Also, studies in septic patients who received G-CSF supplementation to bolster neutrophil function revealed no demonstrable benefit (1417). Accordingly, sepsis has proven to be an extremely complex process wherein attempts to block specific signal pathways have proven unsuccessful, likely due to the redundancy inherent to the host immune system.…”
Section: Discussionmentioning
confidence: 99%
“…[64] Meta-analyses of human studies using granulocyte-colony stimulating factor (G-CSF) and GM-CSF for sepsis have shown no clear-cut benefit in terms of mortality but do demonstrate improved reversal rates from infection. [6566] Further studies looking at G-CSF or GM-CSF therapy based upon monocyte HLA-DR patterns in sepsis are needed. Similarly, studies on IFN-γ in carefully selected patients with low monocytic HLA-DR expression have shown improvement in the deficient HLA-DR expression and cytokine profile of septic patients.…”
Section: Immunomodulating Therapies In Sepsismentioning
confidence: 99%
“…135 However, a recent meta-analysis of the use G-CSF in patients with severe sepsis and septic shock showed no benefit. 136 Whether G-CSF has a special benefit in patients with cirrhosis remains unknown.…”
Section: Granulocyte Colony-stimulating Factormentioning
confidence: 99%